2017
DOI: 10.1186/s13570-017-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of pastoralists’ choice of camel production in Karamoja sub-region, Uganda

Abstract: Camel production is a potential avenue for improved food and income security in dryland areas of East Africa. Despite this potential, there is a dearth of information on the increasing choice of camel production among pastoralists in the region. Camel-owning households were obtained through snowball sampling approach whereas those without camels were obtained randomly in the vicinity of those who had camels. A total of 116 respondents were interviewed in Moroto and Amudat districts of the Karamoja sub-region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…During a focused group discussion among the participants, it was noted that daily reporting of children is vital to the owner in terms of the health characteristics of the particular animal by observing feeding and water activities. According to Salamula et al (2017), practically all members of the household were involved in various camel management tasks, and defined roles and responsibilities were assigned. This finding is supported by Tadesse et al (2015), who found that all camel management tasks are divided among family members, except breeding and marketing decisions, which are mostly the responsibility of men.…”
Section: Camel Production and Settlement Systemmentioning
confidence: 99%
“…During a focused group discussion among the participants, it was noted that daily reporting of children is vital to the owner in terms of the health characteristics of the particular animal by observing feeding and water activities. According to Salamula et al (2017), practically all members of the household were involved in various camel management tasks, and defined roles and responsibilities were assigned. This finding is supported by Tadesse et al (2015), who found that all camel management tasks are divided among family members, except breeding and marketing decisions, which are mostly the responsibility of men.…”
Section: Camel Production and Settlement Systemmentioning
confidence: 99%
“…As a large and valuable livestock species, camels are more likely to be owned by wealthier households. For example, a recent study in Rupa sub-county in Moroto District and Loroo and Amudat sub-counties in Amudat District reported that camels owned by 45% of households, and these households had above-average income (Salamula et al 2017). Camels represented 44.7% of herd composition in terms of TLU.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Watson and Van Binsbergen (2008), Watson, Kochore and Dabassso (2016), Martínez García et al, (2015), results also revealed that large livestock holding is a sign of wealth among pastoralists and wealth often positively associated with new technology adoption which leads to livestock improvement. Camels are desert animals known for its resistant to harsh environment and produce milk during dry seasons and drought years when milk from other livestock species are scarce (Farah et al, 2004 andSalamula et al, 2017).…”
Section: Socio-economic Determinants Of Camel Productionmentioning
confidence: 99%
“…Pastoralism is a culture, mode of production, in Africa especially in the horn whereby pastoralists depend on their livestock (Camel, Sheep and Goats, Cattle), they migrate seasonally due to rainfall and pasture availability. Many scholars defined pastoralism as proud livestock based production system, which is mainly extensive in nature (Hatfield and Davies, 2006;Mukherji et al, 2017).…”
Section: Introductionmentioning
confidence: 99%